EMPOWERING 21ST CENTURY SKILL IN DISTANCE LEARNING THROUGH ELECTROLYTE SOLUTION ASSIGNMENTS AT SMAN 2 CIKAMPEK - Abdul Rosid (JCER (Journal of Chemistry Education Research), 2022)
The research aims to capture the ability and measure the collaboration index of students in conducting and presenting experimental results, involving 252 respondents using the case study method. The aspect of showing the ability to work effectively, being able to appreciate team differences has an index of 81.41% with a VERY STRONG interpretation, "taking responsibility together in collaborative work and appreciating contributions made by team members" has an index of 67.55% with an interpretation SRONG, “shows flexibility and is willing to accept other people's opinions in achieving goals” has an index of 79.8% with a STRONG interpretation